SOLUTE TRANSPORT IN A POROUS MEDIUM WITH PIECEWISE HOMOGENEOUS SALINIZATION (American Journal of Technology and Applied Sciences, 2026)
In the paper a problem of salt transport in a porous medium with picewise salinization is numerically solved. Two cases are considered: 1) bed with immoile liquid zone saturated with salt solution; 2) dry bed with picewise salinization. Influence of salt adsorption on salt transport characteristics is established.